BRCA1-regulated RRM2 expression protects glioblastoma cells from endogenous replication stress and promotes tumorigenicity - Rasmussen, Rikke D; Gajjar, Madhavsai K; Tuckova, Lucie; Jensen, Kamilla E; Maya-Mendoza, Apolinar; Holst, Camilla B; Møllgaard, Kjeld; Rasmussen, Jane S; Brennum, Jannick; Bartek, Jiri; Syrucek, Martin; Sedlakova, Eva; et al. (Nature communications, 2016)
Oncogene-evoked replication stress (RS) fuels genomic instability in diverse cancer types. Here we report that BRCA1, traditionally regarded a tumour suppressor, plays an unexpected tumour-promoting role in glioblastoma (GBM), safeguarding a protective response to supraphysiological RS levels. Higher BRCA1 positivity is associated with shorter survival of glioma patients and the abrogation of BRCA1 function in GBM enhances RS, DNA damage (DD) accumulation and impairs tumour growth. Mechanistically, we identify a novel role of BRCA1 as a transcriptional co-activator of RRM2 (catalytic subunit of ribonucleotide reductase), whereby BRCA1-mediated RRM2 expression protects GBM cells from endogenous RS, DD and apoptosis. Notably, we show that treatment with a RRM2 inhibitor triapine reproduces the BRCA1-depletion GBM-repressive phenotypes and sensitizes GBM cells to PARP inhibition. We propose that GBM cells are addicted to the RS-protective role of the BRCA1-RRM2 axis, targeting of which may represent a novel paradigm for therapeutic intervention in GBM.
Keywords: regulace genové exprese u nádorů; Animals; ribonukleosiddifosfátreduktasa; Cell Line, Tumor; BRCA1 Protein; Mice, Nude; Gene Expression Regulation, Neoplastic; nádory mozku; lidé; Survival Analysis; replikace DNA; nádorové buňky kultivované; transplantace heterologní; Mice, Inbred BALB C; Carcinogenesis; Transplantation, Heterologous; glioblastom; Glioblastoma; karcinogeneze; Ribonucleoside Diphosphate Reductase; retrospektivní studie; Tumor Cells, Cultured; myši inbrední BALB C; protein BRCA1; Brain Neoplasms; RNA Interference; analýza přežití; zvířata; RNA interference; DNA Replication; Retrospective Studies; myši nahé; nádorové buněčné linie; Humans